2018
DOI: 10.1186/s40345-018-0123-y
|View full text |Cite
|
Sign up to set email alerts
|

Lack of emotional gaze preferences using eye-tracking in remitted bipolar I disorder

Abstract: BackgroundBipolar disorder is associated with heightened and persistent positive emotion (Gruber in Curr Dir Psychol Sci 20:217–221, 2011; Johnson in Clin Psychol Rev 25:241–262, 2005). Yet little is known about information processing biases that may influence these patterns of emotion responding.MethodsThe current study adopted eye-tracking methodology as a continuous measure of sustained overt attention to monitor gaze preferences during passive viewing of positive, negative, and neutral standardized photo s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 86 publications
0
8
0
1
Order By: Relevance
“…bipolar disorder; e.g. García-Blanco et al, 2014;2017;Leyman et al, 2009;Purcell et al, 2018). Our participants likely differ in several important dimensions from the clinically recruited BD populations in these studies that may explain observed differences, including age, medication status, prior depression history and common comorbid disorders, as well as the effects of sustained illness duration.…”
Section: Discussionmentioning
confidence: 85%
“…bipolar disorder; e.g. García-Blanco et al, 2014;2017;Leyman et al, 2009;Purcell et al, 2018). Our participants likely differ in several important dimensions from the clinically recruited BD populations in these studies that may explain observed differences, including age, medication status, prior depression history and common comorbid disorders, as well as the effects of sustained illness duration.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, some studies find no evidence of positive biases (e.g. Peckham et al, 2016;Purcell et al, 2018), while others find that some with bipolar disorder show negative biases and negative appraisals of internal states (e.g. Lyon et al, 1999;Mansell et al, 2007).…”
Section: Interpretation Bias and Bipolar Disordermentioning
confidence: 95%
“…Eye gaze in particular has been identified as playing a key role in communication, with infants showing a preference for direct gaze from birth (Farroni et al, 2002 ). The role that eye gaze plays in social interaction has been studied across a variety of fields, including typical and atypical child development (Baron-Cohen, 1997 ; Morales et al, 2000 ), mental health conditions [including schizophrenia (Dowiasch et al, 2016 ); posttraumatic stress disorder (Lazarov et al, 2019 ), and bipolar disorder (Purcell et al, 2018 )], primates (Ryan et al, 2019 ) and human-robot interaction (Admoni and Scassellati, 2017 ). Additionally, eye gaze has been studied with different theoretical and methodological approaches from neuroscience (Sato et al, 2016 ) to sociology (McCarthy et al, 2008 ), producing a rich variety of data but complicating the conclusions that can be drawn about the role of eye-gaze in conversation.…”
Section: Introductionmentioning
confidence: 99%